The Utilization of Rasch Model Measurement (RMM) in Investigating the Effect of Pharmacological and Non-pharmacological Treatment on the Quality of Life of Malaysian’s Children with Autism Spectrum Disorder (ASD) and Their Family - Fikry, Amily; Mahamood, Siti Fatahiyah; Mamat, Mohd Nor; Hassan, Hamizah (Journal of Social Transformation and Regional Development, 2020)
Autism Spectrum Disorder (ASD) is a developmental disorder that encompasses varieties of disorder with impairments in social relationships, communication and imaginative display. In an attempt to reduce the severity of the said symptoms, these ASD children have been given either pharmacological or non-pharmacological treatment. The treatment given is hope to improve quality of life of the ASD children and their respective family. Thus, by using Rasch Model, this paper attempts to look at the significant effect of pharmacological and non-pharmacological treatment on quality of life of Malaysian’s children with Autism and their respective family. A total of 31 questionnaires (with 16 returned and usable questionnaires) were distributed to parents of ASD child at public rehab center located in Eastern and Central Region of Malaysia. By using Bond and Fox Steps of Rasch Measurement Model, reliability analysis of responses were analyzed and research questions were answered. Conclusions and recommendations were discussed at the end of the paper.